2022
DOI: 10.1002/aenm.202200113
|View full text |Cite
|
Sign up to set email alerts
|

Homologous MXene‐Derived Electrodes for Potassium‐Ion Full Batteries

Abstract: The development of potassium‐ion battery (PIB) electrode materials is critical for promoting their use in next‐generation energy storage systems. Although metal–organic frameworks (MOFs) are appealing electrode materials, their performance in PIBs remains unsatisfactory. The low K+ adsorption energy (ΔEa) on the saturated coordination of MOFs can explain the limited capacity. Herein, MXene‐derived MOF nodes (NMD‐MOF) are unlocked and used as anodes in PIB. The NMD‐MOF anode exhibits substantially increased cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…In terms of electrode material innovation, Wu and coworkers reported an unexplored node-unlocked 2D metal organic framework (MOF) nanosheet anode material and K + intercalated vanadium oxide nanoribbon cathode material, both from V 2 CT x (T x = terminal atom) MXene. [151] They assembled these two materials into a potassium ion full cell and found that the system achieved a specific capacity of 63 mAh g −1 at 50 mA g −1 and a high energy of 143 Wh kg −1 and a power density of 440 W kg −1 . The excellent performance of this full cell is mainly due to the advantage of MXene over other soluble metal precursors in the preparation of nano-MOFs, resulting in homogeneous terminal atoms with high electronegativity, which allows the organic ligands to rapidly deprotonate and bind to the underlying metal atoms.…”
Section: Full-cells Developmentmentioning
confidence: 99%
“…In terms of electrode material innovation, Wu and coworkers reported an unexplored node-unlocked 2D metal organic framework (MOF) nanosheet anode material and K + intercalated vanadium oxide nanoribbon cathode material, both from V 2 CT x (T x = terminal atom) MXene. [151] They assembled these two materials into a potassium ion full cell and found that the system achieved a specific capacity of 63 mAh g −1 at 50 mA g −1 and a high energy of 143 Wh kg −1 and a power density of 440 W kg −1 . The excellent performance of this full cell is mainly due to the advantage of MXene over other soluble metal precursors in the preparation of nano-MOFs, resulting in homogeneous terminal atoms with high electronegativity, which allows the organic ligands to rapidly deprotonate and bind to the underlying metal atoms.…”
Section: Full-cells Developmentmentioning
confidence: 99%
“…Over the past decades, as the requirements for large-scale energy storage systems grow up, concerns over the scarcity of mineral resources and high cost of lithium-ion batteries (LIBs) have raised rapidly . Sodium (Na) and potassium (K), from the same group as lithium (Li), have been placed with great expectations due to their similar physicochemical properties as well as comparable potential to that of Li/Li + . However, most electrode materials of LIBs are difficult to be used in sodium-ion batteries (SIBs) as well as potassium-ion batteries (PIBs) directly due to severe volume change caused by the large radius of Na + and K + and sluggish reaction kinetics during charge/discharge .…”
Section: Introductionmentioning
confidence: 99%
“…1 Sodium (Na) and potassium (K), from the same group as lithium (Li), have been placed with great expectations due to their similar physicochemical properties as well as comparable potential to that of Li/Li + . 2 However, most electrode materials of LIBs are difficult to be used in sodiumion batteries (SIBs) as well as potassium-ion batteries (PIBs) directly due to severe volume change caused by the large radius of Na + and K + and sluggish reaction kinetics during charge/ discharge. 3 Hence, there is in urgent need of designing more suitable electrode materials for next generation SIBs and PIBs.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the ultra-thin layer structure, homogeneous negatively charged functional groups, thermodynamically metastable metal atoms and various element composition, MXene could act as nucleating sites to enable the easily formed of the derivatives. [12,[16][17][18] The Titanium-based polyanionic compounds, which possess the inorganic-open framework favorable for ion transport and relatively low redox potential for potassium ions, are considered to be an effective anode with high abundance, low-cost, excellent stability, and environmental friendly. [6,[19][20][21] Sun et al reported a KTiOPO 4 anode with small lattice strain during K + intercalation.…”
mentioning
confidence: 99%